9a+10(6aq-1)=

Simple and best practice solution for 9a+10(6aq-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9a+10(6aq-1)= equation:


Simplifying
9a + 10(6aq + -1) = 0

Reorder the terms:
9a + 10(-1 + 6aq) = 0
9a + (-1 * 10 + 6aq * 10) = 0
9a + (-10 + 60aq) = 0

Reorder the terms:
-10 + 9a + 60aq = 0

Solving
-10 + 9a + 60aq = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 9a + 10 + 60aq = 0 + 10

Reorder the terms:
-10 + 10 + 9a + 60aq = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 9a + 60aq = 0 + 10
9a + 60aq = 0 + 10

Combine like terms: 0 + 10 = 10
9a + 60aq = 10

Reorder the terms:
-10 + 9a + 60aq = 10 + -10

Combine like terms: 10 + -10 = 0
-10 + 9a + 60aq = 0

The solution to this equation could not be determined.

See similar equations:

| X-4=-5.6 | | -2x^3+3x^2-x-36=48 | | -2x^3+3x^2-x-36=38 | | -2x^3+3x^2-x-36=36 | | -2x^3+3x^2-x-36=24 | | -3x-2x=7 | | 2b+17=41 | | 32x^2-34+40=0 | | 18x-xy+7x=5x+20 | | -7(4+6k)=-4(9x-11)+9 | | 5cosX+6=4 | | 3y-5=0.5*4y+2 | | -5n+3(3+7n)= | | a(n)=n+0.6(n-1) | | (3+3)-3= | | -x-9=6x+5 | | a(21)=-1.4 | | (3+a)-3= | | 2.4=6f | | 8x=4x+48 | | 4x+2x=5x+x | | 4p-4=6p-4-2p | | 3x+4x+2x+x=360 | | 2.4=6.4 | | -x-9=-6x+5 | | Logx=0.55 | | .35x+8=21 | | 6x^2+3x+-180=0 | | 3+2.4x=1 | | 4x+4(x+7)=128 | | p=-5.4+-0.4q | | x+123456789=0 |

Equations solver categories